ANALISIS HUKUM PENERAPAN ASESMEN TERHADAP KORBAN PENYALAHGUNAAN NARKOTIKA PADA KEPOLISIAN REPUBLIK INDONESIA - Wilson Bugner Pasaribu; Syafruddin Kalo; Suhaidi Suhaidi; Mahmud Mulyadi (Universitas Sumatera Utara, 2018)
ABSTRACT Police involvement in the assessment team is an important part in the handling of narcotic addicts because in Law no. 35 Year 2009 on Narcotics including the investigators other than BNN. Although in Law no. 35 of 2009 on Narcotics BNN's portion of authority for narcotic crime is greater than that of the police. Therefore, it is necessary to review the assessment of assessment in rehabilitating victims of narcotics abuse. Obligation of rehabilitation against narcotics abuse. Implementation of the assessment of victims of narcotics abuse in the Police of the Republic of Indonesia. Keywords: Assessment, Narcotics And Addicts Crime